2020
DOI: 10.1038/s41598-020-77599-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence algorithm for detecting myocardial infarction using six-lead electrocardiography

Abstract: Rapid diagnosis of myocardial infarction (MI) using electrocardiography (ECG) is the cornerstone of effective treatment and prevention of mortality; however, conventional interpretation methods has low reliability for detecting MI and is difficulty to apply to limb 6-lead ECG based life type or wearable devices. We developed and validated a deep learning-based artificial intelligence algorithm (DLA) for detecting MI using 6-lead ECG. A total of 412,461 ECGs were used to develop a variational autoencoder (VAE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…The most important aspect of deep learning is its ability to extract features and develop an algorithm using various types of data, such as images, 2D data, and waveforms. In previous studies, Attia and colleagues and our study group developed a deep learning‐based model to screen for heart failure, arrhythmia, valvular heart disease, left ventricular hypertrophy, and anemia (Attia, Friedman, et al., 2019; Attia, Kapa, et al., 2019; Attia, Noseworthy, et al., 2019; Cho et al., 2020; Galloway et al., 2019; Jo et al., 2020; Kwon, Cho, et al., 2020; Kwon, Kim, et al., 2020; Kwon, Lee, et al., 2020). In recent studies, Attia and colleagues showed that hyperkalemia and hypokalemia could be detected using ECG based on a deep learning model (Galloway et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important aspect of deep learning is its ability to extract features and develop an algorithm using various types of data, such as images, 2D data, and waveforms. In previous studies, Attia and colleagues and our study group developed a deep learning‐based model to screen for heart failure, arrhythmia, valvular heart disease, left ventricular hypertrophy, and anemia (Attia, Friedman, et al., 2019; Attia, Kapa, et al., 2019; Attia, Noseworthy, et al., 2019; Cho et al., 2020; Galloway et al., 2019; Jo et al., 2020; Kwon, Cho, et al., 2020; Kwon, Kim, et al., 2020; Kwon, Lee, et al., 2020). In recent studies, Attia and colleagues showed that hyperkalemia and hypokalemia could be detected using ECG based on a deep learning model (Galloway et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis is that limb 6‐lead ECG already had information on precordial 6‐lead ECG. In previous studies, Cho et al have already developed a model to generate precordial 6‐lead ECG from limb 6‐lead ECG (Cho et al., 2020). In some tasks, information about the specific disease of precordial 6‐lead is already reflected in limb 6‐lead ECG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of ECG-based AI algorithms have shown great performance in detecting cardiac conditions, such as LVSD [ 117 , 118 ], HCM [ 119 ] and MI [ 120 ]. The performance of these AI algorithms is typically better than risk scores currently used in routine practice, e.g., the CHA 2 DS 2 -VASc score.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The application of this technology in numerous healthcare and medical fields acting as a decision assistance tool will provide aid from diagnosis to prognosis [6]. For example, detecting a myocardial infarction using a six lead ECG with a validated deep learning bases AI algorithm [7]. The application of these technologies is to minimize the loss caused by this pandemic.…”
Section: Introductionmentioning
confidence: 99%